Posttraumatic Skin and Soft-Tissue Infection due to Pseudomonas fulva - Fernando Cobo; Gemma Jiménez; Javier Rodríguez-Granger; Antonio Sampedro (Case Reports in Infectious Diseases)
We report a case of posttraumatic skin and soft-tissue infection in a patient with a left thigh wound after a traffic accident. Pseudomonas fulva was isolated from a wound aspirate and was identified to the species level by Maldi-tof. The patient responded to drainage, debridement of wound, and two weeks of intravenous antibiotic therapy. Follow-up after 3 weeks was satisfactory with healthy cover of the injured area.